2011
DOI: 10.1242/jcs.077172
|View full text |Cite
|
Sign up to set email alerts
|

Isoaspartate-dependent molecular switches for integrin–ligand recognition

Abstract: Formation of isoAsp in ECM proteins and its functional effects Formation of isoAsp and ECM protein damageThe formation of isoAsp residues at Asn or Asp residues in proteins is generally considered a degradation reaction as a consequence of protein aging. IsoAsp formation has been shown to occur in ECM proteins, including collagen types I and III, in fibronectin, in -crystallin and in the ECM of the mammalian brain (Lanthier and Desrosiers, 2004;Lindner and Helliger, 2001; Reissner and Aswad, SummaryIntegrins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 68 publications
(103 reference statements)
1
67
0
Order By: Relevance
“…Integrin b1 and b3 contact the N-terminal domain of TG2, which contains a DGR motif. An aspartate residue in the DGR motif has been reported to undergo posttranslational modification to form an iso-DGR motif that mimics a well-known integrin binding RGD motif [168]. Syndecan-4 targets the 208-217 AA ID region, which contains several phosphorylation sites.…”
Section: -21mentioning
confidence: 99%
“…Integrin b1 and b3 contact the N-terminal domain of TG2, which contains a DGR motif. An aspartate residue in the DGR motif has been reported to undergo posttranslational modification to form an iso-DGR motif that mimics a well-known integrin binding RGD motif [168]. Syndecan-4 targets the 208-217 AA ID region, which contains several phosphorylation sites.…”
Section: -21mentioning
confidence: 99%
“…After washing and blocking with 3% BSA-DPBS, the plates were seeded with HaCaT, EA.hy926, and T98G cells diluted in 0.1% BSA-DMEM (40,000 cells/well) and left to adhere for 3 h at 37°C. Adherent cells were fixed and stained with crystal violet as described (14), and adhesion was evaluated as adsorbance at 570 nm. For each treatment condition, cell spreading was evaluated comparing cell area in different microscopy fields.…”
Section: Cell Adhesion Assay and Protein L-isoaspartyl Methyltransfermentioning
confidence: 99%
“…As molecular switches, formation of isoAsp residues in integrin ligands by Asn deamidation or Asp dehydration could participate in regulation of integrin signaling via the mechanism of increased binding activity. [50] Furthermore, recent study demonstrated that epithelial mesenchymal transition (EMT) occurred through integrin signaling in association with TGF-β signaling. [51] The increasing amounts of evidence for EMT in pathology of IPF and COPD are documented.…”
Section: Discussionmentioning
confidence: 99%